A 3D re-entrant structural metamaterial with negative Poisson's ratio reinforced by adding arrow structures. (1st March 2023) - Wang, Jie; Wu, Zongze; Xiao, Rui; Tang, Changyu; Xu, Yangguang
Abstract: Structural metamaterial with negative Poisson's ratio often has low stiffness due to its porous structure. For engineering applications, the various strategies have been developed to enhance its stiffness but also weaken the negative Poisson effect. In this work, we propose a 3D reinforced re-entrant structure (RRS) by adding arrow structures to the classical re-entrant structure (RS), which is fabricated by photocuring 3D printing of photosensitive resin. The structure-properties correlative mechanism of RRS is systematically analyzed by combining experiment (quasi-static compression experiment) and finite element simulation (ABAQUS). It is found that the equivalent elastic modulus and negative Poisson's ratio of RRS can be tuned by various structural parameters (i.e. the thickness ratio η, the length ratio of the slant rod α, the length ratio of the vertical rod β, and the angle θ of the re-entrant cells). By optimizing the structure parameters, the equivalent elastic modulus of RRS with the negative Poisson's ratio of −0.28 can be significantly increase to 13.67 MPa, which is 12.32 times larger than that of RS with the same negative Poisson's ratio. Due to the flexible design of stiffness and negative Poisson ratio, our proposed 3D reinforced re-entrant structural metamaterial provides a potential way for designing engineering materials with desirable performance.